Gender policy Challenges: definitions, history and global public policies for black, indigenous and women of the periphery - McGill, Eugenia (Esferas, 2020)
Eugenia Mcgill is a professor at the School of International and Public Affairs at Columbia University. She granted this interview to Esferas Journal addressing the topic of gender equality public policies and the importance of this field in academic research, in society and in the global context. Professor McGill discussed the need for society to understand what gender issues are, and how they result in inequalities and injustices in countries. The challenge is to build a global agenda to eradicate gender inequalities, especially among black, indigenous, and poor women around the world. In the transcription that follows, we chose to keep the oral aspects of the interview.